2012
DOI: 10.1021/es301692t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lubrication Oil in the Particulate Matter Emissions from Engine Exhaust of In-Service Commercial Aircraft

Abstract: Lubrication oil was identified in the organic particulate matter (PM) emissions of engine exhaust plumes from in-service commercial aircraft at Chicago Midway Airport (MDW) and O'Hare International Airport (ORD). This is the first field study focused on aircraft lubrication oil emissions, and all of the observed plumes described in this work were due to near-idle engine operations. The identification was carried out with an Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF AMS) via a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…One component of the organic PM exhaust we clearly identify as lubrication oil, a known component of aircraft engine PM emissions (Timko et al 2010b;Yu et al 2010Yu et al , 2012. Yu et al (2010) studied lubrication oil PM under well defined laboratory conditions and concluded that the mass spectra of pure synthetic lubrication oils could be differentiated from fuel-related hydrocarbons by strong signals at m/z 85 and 113 combined with weak signals for common ions derived from saturated and unsaturated hydrocarbons (i.e., delta series of 0 and +2 for unsaturated and saturated hydrocarbons, respectively; McLafferty and Tureček 1993).…”
Section: Factor Mass Spectramentioning
confidence: 99%
“…One component of the organic PM exhaust we clearly identify as lubrication oil, a known component of aircraft engine PM emissions (Timko et al 2010b;Yu et al 2010Yu et al , 2012. Yu et al (2010) studied lubrication oil PM under well defined laboratory conditions and concluded that the mass spectra of pure synthetic lubrication oils could be differentiated from fuel-related hydrocarbons by strong signals at m/z 85 and 113 combined with weak signals for common ions derived from saturated and unsaturated hydrocarbons (i.e., delta series of 0 and +2 for unsaturated and saturated hydrocarbons, respectively; McLafferty and Tureček 1993).…”
Section: Factor Mass Spectramentioning
confidence: 99%
“…Some aircraft operations within airports require engines to operate outside their optimal regimes, ranging from a maximum thrust during take-off to low power settings during ground operations. The non-ideal combustion conditions within engines may lead to the emission of by-products, including sulfur oxides, additional nitrogen oxides, unburned hydrocarbons, carbon monoxide and particulate soot (Dakhel et al, 2007;Timko et al, 2010;Yu et al, 2010Yu et al, , 2012Kinsey et al, 2011;Masiol and Harrison, 2014). These substances are emitted within the Planetary Boundary Layer (PBL) during the Landing TakeOff cycle (LTO) and can have plausibly local and direct effects on human health (Ratliff et al, 2009;Levy et al, 2012;Schlenker and Walker, 2012;Ashok et al, 2013;Yim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Timko et al reported significant organic content in PM sampled from idle conditions [26]. Recently both Timko et al [27] and Yu et al [9] found lubrication oil contribution to volatile PM. All such measurements were performed using the Aerodyne aerosol mass spectrometer.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Related work has found oil to contribute to secondary organics by overboard venting of the recirculation system through the engine nacelle [42] and also by fragmentation patterns of hydrocarbons of vented vapors within the core flow exhaust [9]. Yet fragmentation patterns, under exhaust flow conditions can be masked given the vast array of other organics produced by incomplete combustion.…”
Section: Elemental Compositionmentioning
confidence: 99%
See 1 more Smart Citation